The Teachers' Transfer Policy, Haryana (2016): A Critical Evaluation. (June 2022) - Sharan, Arushi; Jain, Naman; Vashistha, Prachi; Singh, Pulin
The Teachers' Transfer Policy, 2016, for teachers serving in government schools across Haryana was started with the explicit goal of improving job satisfaction for teachers. It represented a major reform in transfer of teachers in public schools across the state, as prior to this, transfers were mired in political hurdles and corruption. This study adopts a mixed-methods approach to assess teachers' satisfaction with the policy and explores perceptions across the population on whether it affects their work satisfaction too. The study finds that teachers experience the implementation of the policy in a more nuanced way than the officials. It also finds that they exhibit a high level of satisfaction with the policy, but that it is not uniformly distributed. Rather, satisfaction varies by age and preference for allotments. Work satisfaction has been only marginally affected by the policy.